Differences Between Wound Care with Modern Technique and Wound Care with Conventional Technique in Healing Diabetes Mellitus Wound - Harahap, Zainuddin; Harahap, Solihuddin (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Diabetes mellitus is a disease caused by glucose metabolism disorder because there is glucose transportation disorder in cells as the result of the decrease in the work of insulin. Its great impact will influence patientsâ life quality, especially patients with complication in diabetic foot wound. The objective of the research was to find out the differences between wound care with modern technique and wound care with conventional technique in healing diabetes mellitus wound. The research used quasi experimental method with pretest-posttest group design. The population was diabetic wound patients treated in the Praktek Mandiri Perawat (Nurse Independent Practice) Asri Woundcare, Medan, for diabetic wound care with modern and conventional technique at Mitra Sejati Hospital, Medan, and 34 of them were used as the samples. The result of the research showed that most of the respondents were > 49 years old, males, and had foot wound. Diabetes mellitus wound care with modern technique decreased in wound regeneration score of 49.5% while with conventional technique it decreased to 42.5%. There were significant differences between diabetes mellitus wound care with modern technique and that with conventional technique; diabetes mellitus wound care with modern technique was faster than that with conventional technique. It is recommended that SOP in wound care be reviewed in every hospital in order to improve nursing care system, especially in applying modern technique in wound care so that diabetes mellitus patients can feel its benefit. Keywords: Modern wound care, Conventional wound care, Diabetes mellitus